157k views
0 votes
Find the value of the exponent c that makes the

second expression equivalent to the first
expression where x > 0 and y >0
324x^6y^8= 4(square roots of)2^2•3^4•x^2•x^c•y^8*
C=

2 Answers

5 votes

Answer:

C=4

Explanation:

Find the value of the exponent c that makes the second expression equivalent to the-example-1
User Mnementh
by
5.7k points
5 votes

Answer:

C=4

Explanation:

3^4/4.2^2/4.x^6/4.y^8/4=2^2/4.3^4/4.x^(c+2)/4.y^8/2

3.2^1/2.x^3/2.y^2=2^1/2.3.x^(c+2)/4.y^2

x^3/2=x^(c+2)/4

3/2=c+2/4

3.4/2=c+2

6=c+2

c=4

I hope this helps! Good luck

User JWo
by
6.2k points